2016
DOI: 10.4103/1319-2442.174071
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neutrophil gelatinase-associated lipocalin as a marker for the prediction of worsening renal function in children hospitalized for acute heart failure

Abstract: Acute heart failure (AHF) is frequently associated with worsening renal function in adult patients. Neutrophil gelatinase-associated lipocalin (NGAL) serves as an early marker for acute renal tubular injury. To assess the role of plasma NGAL in predicting worsening renal function (WRF) in children with AHF, we studied 30 children hospitalized for AHF; children with history of chronic renal disease or on nephrotoxic drugs were excluded. Twenty age- and sex-matched healthy children were included in the study as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, formulae have been developed to indirectly estimate plasma volume using haemoglobin and/or haematocrit data 42 43. Further research is needed to establish the ability of novel biomarkers such as urinary angiotensinogen,44 neutrophil gelatinase-associated lipocalin,45 46 kidney injury molecule-1,47 interleukin-18,48 49 N -acetyl-β-d-glucosaminidase,50 cystatine C51 52 or a combination of some or all of these could also be used to improve clinical decision-making and therapy. The assessment of diuresis and natriuresis, which reflect both glomerular and tubular function, could offer a strategy to achieve decongestion 50 53 54.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, formulae have been developed to indirectly estimate plasma volume using haemoglobin and/or haematocrit data 42 43. Further research is needed to establish the ability of novel biomarkers such as urinary angiotensinogen,44 neutrophil gelatinase-associated lipocalin,45 46 kidney injury molecule-1,47 interleukin-18,48 49 N -acetyl-β-d-glucosaminidase,50 cystatine C51 52 or a combination of some or all of these could also be used to improve clinical decision-making and therapy. The assessment of diuresis and natriuresis, which reflect both glomerular and tubular function, could offer a strategy to achieve decongestion 50 53 54.…”
Section: Discussionmentioning
confidence: 99%
“…So far it was known that acute heart failure is frequently associated with worsening renal function in adult patients. Although investigations on the role of LCN2 in the heart have only recently begun, a very recent report showed that plasma LCN2 levels can also predict worsening renal function in hospitalized children with acute heart failure (Elsharawy et al, 2016 ). Mechanistically, a recent review on cardiomyopathies discusses how LCN2 can regulate heart failure based on iron overload and iron deficiency (Chan et al, 2015 ).…”
Section: Lcn2 Pathophysiological Expression In Tissuementioning
confidence: 99%
“…In this regard, they compared plasma NGAL level between 30 children with heart failure and 20 healthy children. They concluded that the higher serum level of NGAL at the time of admission in children with acute cardiac failure can be the predictor of the renal function worsening (20). The differences between our study and the study by Elsharawy et al are the number of the patients, type of NGAL measurement (urinary versus plasma), age of the patients (between 0 and18 years old versus 48 month), and the final results( in our study, the average urinary NGAL level was higher in children with CHD compared to healthy children, but this difference was not significant, since in their study, the serum level of NGAL was significantly higher in children with acute cardiac failure compared to the control group).…”
Section: Discussionmentioning
confidence: 99%